Counter space : design and the modern kitchen - Kinchin, Juliet. 4 0 16; O'Connor, Aidan; 5 Museum of Modern Art (New York, N.Y.) (New York : The Museum of Modern Art, 2011)
Discusses the history of the kitchen during the twentieth century, and describes how changes in technology, design, domestic life, space, organization, food, consumerism, politics, and gender role has affected its value in a home.
Catalog of an exhibition held at the Museum of Modern Art, New York, Sept. 15, 2010-May 2, 2011.
Keywords: 2 -- 0; 6; History;Design and construction;History;History;History;Design and construction;History;History -- Kitchens;Kitchens;Kitchen utensils;Kitchens;Kitchens;Kitchen utensils -- 20th century;20th century;20th century -- Exhibitions.;Exhibitions.;Exhibitions.;Exhibitions.;Exhibitions.;Exhibitions.; 20; 2